Impact of Silver Nanoparticles on the Surface, Structural-Morphometric, Toxicological, and Antiviral Properties of Photoactive Anatase - Povnitsa, O.Yu.; Artiukh, L.O.; Zaremba, P.Yu.; Yavorovsky, O.P.; Riabovol, V.M.; Tyschenko, N.I.; Lavrynenko, O.M.; Zahorodnia, S.D.; Ievtushenko, A.I.; Zahornyi, M.M.; Повниця, О.Ю.; Артюх, Л.О.; et al. (PH "Akademperiodyka" of the NAS of Ukraine, 2026)
Despite the significant socio-economic consequences of viral diseases, the issue of the quantity and quality of antiviral drugs remains unresolved. Viruses can mutate and become susceptible to treatment. Therefore, the search for various new strategies to combat viral infections remains relevant. Some TiO2&Ag bioactive nanocomposites (NCs) with a specific surface area of 30.65–50.84 m2/g, a point of zero charge (PZC) of nanoparticles of pH 6.2–9.4, depending on the silver content, were chemically synthesized. The purpose of the work was to study the biocompatible, structural-morphometric, toxicological, and virucidal properties of NCs. Methods. NCs based on titanium oxide (IV) with 4% and 8% silver were obtained by modification of TiO2. The structural, surface, toxicological, and hygienic characteristics of TiO2, TiO2&Ag (4 mass% Ag), and TiO2&Ag (8 mass% Ag) nanopowders were studied. For the toxicological and hygienic assessment, the following methods were used: general toxicity, inductively coupled plasma optical emission spectroscopy, immunological methods, and evaluation of the functional state of boar sperm. The preparation of mouse kidney samples for morphological examination was carried out by standard methods with staining using Sirius Red and Weigert's hematoxylin. The cytotoxic effect of substances was studied using the MTT assay. Virucidal activity was determined against human adenovirus serotype 2 (HAdV-2), herpes simplex virus type 1 (HSV-1, strain US), influenza virus type A, (H1N1) strain A/FM/1/4; the contact time with NC was 60 min. Results. The modification of titanium dioxide nanoparticles with silver leads to a significant increase in the adsorption, catalytic, and chemical activity of the surface of TiO₂&Ag, which ultimately results in enhanced biological activity. This leads to a significant increase in the general toxic effects of TiO₂&Ag compared to nano-TiO₂, greater accumulation of titanium in the liver of mice, manifestation of immunotoxic effects, and inhibitory action on boar sperm. Compared to nano-TiO₂, nano-TiO₂&Ag causes more pronounced initial morphological changes in the organ responsible for excreting metal nanoparticles—the kidneys and more effectively crosses the blood-brain barrier. The toxic effect of NCs in the cell lines and the virucidal effect against model RNA and DNA virusesinfluenza A virus (N1H1), human adenovirus (HAdV-2), herpes simplex virus type 1 (HSV-1) were investigated. The greatest toxicity of NCs was shown in human laryngeal carcinoma Hep-2 tumor cells and Syrian hamster kidneys. A significant virucidal effect of NCs was revealed against all viruses within 60 min of contact, viruses were completely inactivated; and the titer of influenza virus decreased by 10 lg, adenovirus – by 7.4 lg, and herpes simplex virus – by 5 lg. Conclusions. The created nanocomposites can be used to inactivate RNA- and DNA-containing viruses outside the cell (by disinfection of surfaces, liquids, and air) in line with the reduction of their toxic properties.